Induced pluripotent stem cell line (INSAi001-A) from a Gaucher disease type 3 patient compound heterozygote for mutations in the GBA1 gene - Duarte, Ana Joana (2020)
The authors thank Hildeberto Correia (Department of Human Genetics in Lisbon), for the karyotype analysis; José Ferrão (Department of Human Genetics in Lisbon), for the STR analysis; the collaboration of the central core services of Department of Human Genetics in Lisbon is acknowledge as well as Meghan Quint for assistance with English language.